2012
DOI: 10.1145/2215676.2215691
|View full text |Cite
|
Sign up to set email alerts
|

Time-aware approaches to information retrieval

Abstract: In this thesis, we address major challenges in searching temporal document collections. In such collections, documents are created and/or edited over time. Examples of temporal document collections are web archives, news archives, blogs, personal emails and enterprise documents. Unfortunately, traditional IR approaches based on term-matching only can give unsatisfactory results when searching temporal document collections. The reason for this is twofold: the contents of documents are strongly time-dependent, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 119 publications
(252 reference statements)
0
3
0
Order By: Relevance
“…Here, we design a ranking model which is based on a mixture model used for IR [25] that linearly combines keywords similarity and temporal similarity and then we map it into XML objects. Given a single temporal object Ot and a temporal query Qt, we compute the similarity degree ρ s of Ot to Qt using the following formula:…”
Section: A Ranking Modelmentioning
confidence: 99%
“…Here, we design a ranking model which is based on a mixture model used for IR [25] that linearly combines keywords similarity and temporal similarity and then we map it into XML objects. Given a single temporal object Ot and a temporal query Qt, we compute the similarity degree ρ s of Ot to Qt using the following formula:…”
Section: A Ranking Modelmentioning
confidence: 99%
“…For example, the Wikipedia pages have different versions that these versions are created by different people to improve the content of the pages. Previous researches [1][2][3][4][5][6][7][8][9][10][11] have shown that investigating on these changes can improve the efficiency of information retrieval systems.…”
Section: Introductionmentioning
confidence: 99%
“…Research on temporal information aiming at free-text EHR includes temporal information extraction [10], temporal pattern mining for classification [11] and temporal order extraction for drug-disease pair [12]. On the other hand, temporal information is also explored in IR on other datasets [13] including microblog [14] and academic literature [15]. However, how to integrate temporal information into IR for EHR still remains a challenge.…”
Section: Introduction and Related Workmentioning
confidence: 99%